Proposta para uma abordagem do conceito de oxirredução no Programa Nacional de Integração da Educação Profissional com a Educação Básica na modalidade de Educação de Jovens e Adultos Educação Profissional Técnica de Nível Médio (PROEJA) - Alves, Rogério Gomes (2013)
The National Program of Professional Education Integration with Basic Education for Youngsters and Adults (PROEJA) Technical Professional Education Ensino Médio has opened a new chapter in the history of education in Brazil, making possible the integration of basic education and professional education. This new form of education, which is still in its early implementation, presents a series of challenges to be overcome. Specifically about the teaching of Chemistry, didactic material to match PROEJA s specific needs is practically inexistent. Thus, this work has the purpose of developing didactic material for the teaching of Chemistry for Professional and Technological Education of Youngsters and Adults in the courses of Electronics, Technical Electronics and Maintenance and Support for Computing at Instituto Federal de Educação,Ciência e Tecnologia do Rio Grande do Norte. This material aims at working chemical concepts of oxi-reduction reactions through a theme approach following Freire s conceptions for the teaching of Youngsters and Adults